High prevalence of intramural coronary infection in patients with drug-resistant cardiac syndrome X: comparison with chronic stable angina and normal controls. Issue 23 (3rd October 2010) - Chimenti, Cristina; Sale, Patrizio; Verardo, Romina; Cicalini, Stefania; Petrosillo, Nicola; Russo, Matteo A; Fedele, Francesco; Frustaci, Andrea
Abstract : Background: Coronary microvascular dysfunction has been reported along with myocardial viral infection. Whether intramural coronary vessels infection plays a role in patients with cardiac syndrome X (CSX) is unknown. Methods: Thirteen consecutive patients (four men, nine women, mean age 51±10.5 years) with drug-resistant CSX underwent left ventricular endomyocardial biopsy. Myocardial tissue was examined for histology, immunohistochemistry and for the presence of cardiotropic viruses by PCR analysis. In the presence of a viral infection on the whole tissue, laser microdissection was performed to analyse the viral genome selectively in intramural vessels and cardiomyocytes. Controls were surgical cardiac biopsies from patients with chronic stable angina and from patients with mitral stenosis and normal cardiac function (normal controls). Results: Histology showed hypertrophy and degeneration of cardiomyocytes with interstitial and replacement fibrosis in all CSX, while focal lymphocytic myocarditis was additionally recognised in three patients. No vasculitis was observed. Viral genomes were detected in nine of 13 CSX (Epstein–Barr virus in four, adenovirus in three, human herpes virus (HHV) 6 in one, Epstein–Barr adenovirus co-infection in one). Laser microdissection showed that Epstein–Barr and adenovirus localised both in cardiomyocytes and intramural vessels, while HHV-6 infection was confined to the vessel wall. Conclusions: Viral genomes can be detected in intramural vessels of up to 69% of drug-resistant CSX. Coronary small vessels infection represents an alternative pathophysiological mechanism of this syndrome and can explain the poor response to anti-ischaemic drugs.